A geographic test of species selection using planktonic foraminifera during the Cretaceous/Paleogene mass extinction. Issue 3 (8th April 2011) - Powell, Matthew G.; MacGregor, Johnryan
Abstract : Species selection has received a great deal of theoretical attention but it has rarely been empirically tested. It is important to determine the level of selection that operated during a particular extinction event because it can help distinguish between traits that were actually responsible for extinction and those that were merely correlated with it. Here, we present a test that can help distinguish between organismal and species-level selection, which we demonstrate using the high-resolution fossil record of planktonic foraminifera species recorded in deep-sea sediment cores. Our test examines the fate of survivors and victims during the Cretaceous/Paleogene (K/Pg) mass extinction within single geographic regions, where all individuals experience the same selection pressures. Selection at the organismal level implies that individual members of surviving species are more fit than those of victimized species, and therefore should be more likely to survive in affected areas; conversely, selection at the species level implies individuals will suffer equally within an affected area. We find that survivors of the mass extinction suffered very high extirpation rates in cores where the overall extinction rate was high, indicating that individual members of the surviving species were generally no more fit than individual members of extinct species. Rather, these species were able to survive because they possessed advantageous species-level traits, such as larger geographic ranges and greater abundances than victimized species. This geographic pattern of extirpation suggests that selection operated at the species, rather than organismal, level during the K/Pg mass extinction of planktonic foraminifera.